2018
DOI: 10.1038/s41467-018-07447-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of RIP2 activation and signaling

Abstract: Signals arising from bacterial infections are detected by pathogen recognition receptors (PRRs) and are transduced by specialized adapter proteins in mammalian cells. The Receptor-interacting-serine/threonine-protein kinase 2 (RIPK2 or RIP2) is such an adapter protein that is critical for signal propagation of the Nucleotide-binding-oligomerization-domain-containing proteins 1/2 (NOD1 and NOD2). Dysregulation of this signaling pathway leads to defects in bacterial detection and in some cases autoimmune disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 52 publications
5
70
1
Order By: Relevance
“…Recent in vitro structural data that indicate that the CARD of NOD1 forms a transient unstable complex with RIPK2 CARD to induce aggregation is consistent with our in situ data (Gong et al, 2018). NF-κB signaling thereby seems to be uncoupled from this process as mutations in NOD1 and NOD2 that interfere with NF-κB activation still triggered RIPosome formation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Recent in vitro structural data that indicate that the CARD of NOD1 forms a transient unstable complex with RIPK2 CARD to induce aggregation is consistent with our in situ data (Gong et al, 2018). NF-κB signaling thereby seems to be uncoupled from this process as mutations in NOD1 and NOD2 that interfere with NF-κB activation still triggered RIPosome formation.…”
Section: Discussionsupporting
confidence: 89%
“…Using this tool, we found that RIPosomes formed after NF-κB activation mediated by NOD1, which is contradictory to a direct role of these structures in NF-κB activation by NOD1/2, as recently proposed by others (Gong et al, 2018, Pellegrini et al, 2018. Activation of NF-κB responses by NOD1 and NOD2 is associated with membrane recruitment of NOD1 and NOD2 (Kufer, Kremmer et al, 2008, Lecine, Esmiol et al, 2007, Nakamura, Lill et al, 2014, Travassos, Carneiro et al, 2010.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…4a-b to Fig. 3c-d), which had not been highlighted by previous analyses 20,27,[29][30][31][32][33][34][35] . In ASC-CARD filaments, this bridge consists of two residues Gln185 and Tyr187, which extend from the Type IIb surface and interact with Ala168 and Asn170 on the Type IIa surface ( Fig.…”
Section: Structural Basis For the Distinct Downstream Card Preferencementioning
confidence: 51%
“…In recent studies, higher order intracellular signalling platforms consisting of RIPK2 and NOD receptors were described [36,57,58]. In particular, inhibition of XIAP by either siRNA or by SMAC mimetic compounds led to RIPK2-containing speck-like structures in cells, termed Riposomes [36].…”
Section: Discussionmentioning
confidence: 99%